Riders of destiny - Bradbury, Robert N. (Robert North); Wayne, John, 1907-1979; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1933)
Kincade controls the area's water supply and is about to force the ranchers into contracts at exorbitant rates. Government Agent Saunders has a plan that will open up the lost river and dry up Kincade's supply. --
John Wayne, Cecilia Parker, Forest Taylor, George Hayes, Al St. John, Heinie Conklin, Yakima Canutt, Earl Dwire, Lafe Mckee, Addie Foster.
Cinematographer, Archie Stout; editor, Carl Pierson.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Water rights -- West (U.S.) -- Drama; Real estate business -- Corrupt practices -- West (U.S.) -- Drama; Shooters of firearms -- West (U.S.) -- Drama; Undercover operations -- West (U.S.) -- Drama; Western films; Feature films; Internet videos; Streaming video